Mycotoxicological monitoring. Part 3. Feedstuffs from raw grain processing - G. P. Kononenko; A. A. Burkin; Ye. V. Zotova (Ветеринария сегодня)
The paper presents the results of mycotoxicological testing of the production batches of sunflower cake and meal, feedstuffs of soybean and wheat bran processing received from domestic processing establishments and livestock farms from 2009 to 2019. Detection and measurement of the content of fusariotoxins, including T-2 toxin, diacetoxyscirpenol, deoxynivalenol, zearalenone and fumonisins of B group, as well as alternariol, ochratoxin A, citrinin, aflatoxin B1, sterigmatocystin, cyclopiazonic acid, mycophenolic acid, ergot alkaloids and emodin was carried out by a competitive ELISA in accordance with certified procedure. The summarized results demonstrate the predominant role of alternariol in the contamination of sunflower cake and meal, as well as the frequent occurrence of T-2 toxin, ochratoxin A, citrinin, cyclopiazonic acid, sterigmatocystin, mycophenolic acid and emodin. For the main contaminants, a shift in the medians and 90% percentile towards the lower values of the average and maximum contents was observed, which indicates the possibility of their accumulation beyond the typical range. The summary and results of mycotoxicological study of wheat bran and feedstuffs of soybean processing for a complete list of 14 parameters are presented in this paper for the first time. It was found that the range of mycotoxins that can contaminate soybean meal, cake and full-fat soybean is quite wide, which is consistent with the results of the study of soybean seed mycobiota composition. It was demonstrated that soybean meal can accumulate high concentrations of mycophenolic acid – up to 1,255 μg/kg. As for the wheat bran batches, cases of contamination with diacetoxyscirpenol and the frequent occurrence of T-2 toxin, emodin and ergot alkaloids were detected. The initial monitoring data, systematized and summarized in this paper, are presented in electronic form in the section “Additional materials”. The prospects of testing of feedstuffs from processing other oilseeds, as well as from wheat and corn grain processing are discussed.